PERBEDAAN KEBUTUHAN LAYANAN BK BERDASARKAN TAHAP PERKEMBANGAN USIA DAN IMPLIKASINYA TERHADAP PROGRAM BK INKLUSIF: KAJIAN PUSTAKA - Patriana (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2026)
This research is motivated by the importance of understanding the differences in guidance and counseling (GC) service needs at each stage of developmental age as a basis for designing effective and inclusive programs. This study aims to analyze the differences in guidance and counseling (GC) service needs across various developmental stages and their implications for the development of inclusive GC programs. Employing a qualitative approach with a literature study method, this research reviews primary and secondary sources, including books, national and international journal articles, and relevant educational policies. Data were collected through literature review, while data analysis followed the Miles and Huberman model, consisting of (1) data reduction, (2) data display, and (3) conclusion drawing and verification. The validity of the data was ensured through source triangulation. The findings indicate that GC service needs evolve according to developmental stages: elementary school-aged children require support in emotional regulation, social adaptation, and learning readiness; adolescents need services related to identity development, social relationships, and career planning; while young adults require assistance in career counseling, decision-making, and interpersonal skills development.